Challenges of Spiritual Cosmology: Symbolism in Esoteric Texts in Indonesia - Abdullah, Muhammad; Muzakka, Moh.; Rukayah, R. Siti; Pamungkas, Onok Yayang (Journal of Posthumanism, 2025)
Esoteric aspects in the pesantren tradition such as wirid, hizb, wifiq, and rajah are still often marginalized in academic studies, trapped in stigma as mystical artifacts or even misunderstood. This research aims to deconstruct this academic marginalization and examine the metaphysical and ethnological dimensions and esoteric texts of Islamic boarding schools, revealing its role in building a spiritual dialectic that integrates Islamic theology with local wisdom. The research method used is a philological approach, which includes inventory, description, transliteration, translation, and manuscript identification. In addition, focus group discussions (FGD) were implemented to enrich textual analysis and explore the meanings contained in the cultural context of Islamic boarding schools. The results of the study show that wirid and hizb, with a certain repetitive and kaifiyah structure, not only function as ritualistic means, but also as a transcendental gateway to the presence of the Divine. Wifiq and diagrams, with their intricate symbolic and numerical configurations, reflect a cosmological order that confirms man’s connection to greater spiritual power. This research underlines that the esoteric texts of pesantren act as an epistemic device that unites the world of transitoral materials, offering spiritual insights that remain relevant in the modern era. The implications of this study encourage interdisciplinary studies that integrate Islamic studies, anthropology, and philosophy, while opening up space for comparative exploration with global esoteric traditions to enrich understanding of human spiritual complexity.